Drug release kinetics of pH‐responsive microgels of different glass‐transition temperatures. Issue 13 (25th November 2018) - Islam, M. S.; Tan, J. P. K.; Kwok, C. Y.; Tam, K. C.
ABSTRACT: The pH‐responsive microgels (MGs) consisting of methacrylic acid‐ethyl acrylate (MAA‐EA), methacrylic acid‐butyl methacrylate (MAA‐BMA) or methacrylic acid‐methyl methacrylate (MAA‐MMA) crosslinked with di‐allyl phthalate (DAP) were synthesized via emulsion polymerization. It was found that the energy required to extract a proton from MGs with higher glass‐transition temperature ( T g ) was greater than at a lower T g . Procaine hydrochloride (PrHy) was used to study the release of a model hydrophobic drug from MGs with different T g s. A drug selective electrode (DSE) was used to monitor the release as a function of pHs and T g s. With increasing pH or decreasing T g, the swelling of MGs was enhanced, leading to greater release of the drug. From the Berens and Hopfenberg model, the contributions of chain relaxation and diffusion processes during a release process were determined. The drug release from lower T g MGs and at high pH is dominated by diffusion rather than chain relaxation. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47284. Abstract :